2018
DOI: 10.1371/journal.pone.0205701
|View full text |Cite
|
Sign up to set email alerts
|

In artificial roost comparison, bats show preference for rocket box style

Abstract: Understanding microhabitat preferences of animals is critical for effective conservation, especially for temperate-zone bats, which receive fitness benefits from selecting optimal roost microhabitats. Artificial roost structures are increasingly being used in conservation efforts for at-risk bat species. To evaluate microhabitat differences in common artificial roost structures and determine if roost selection occurs based on structure type, we installed artificial roosts of three different styles (bat box, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 45 publications
(67 reference statements)
1
40
0
1
Order By: Relevance
“…Currently, we lack detailed microclimate profiles for most bat box designs, but several studies have documented temperatures >40°C (maximum roost temperature: >40°C, Bartonička & Řehák, 2007; >50°C, Bideguren et al, 2018; 53°C, Brittingham & Williams, 2000; 54.5°C, Flaquer et al, 2014; 53°C, Griffiths, Rowland, et al, 2017; 61°C for a bark mimic roost, Hoeh, Bakken, Mitchell, & O'Keefe, 2018; >40°C, Kerth, Weissmann, & König, 2001; >50°C, Lourenço & Palmeirim, 2004; 54°C, Tillman, 2019), highlighting that many bat box designs could subject bats to heat stress. Exacerbating this, most published research has focused on novel box designs or modifications, providing data that are less applicable to practitioners and homeowners who are not intent on building or modifying their own boxes.…”
Section: Increasing Popularity Uncertainty and Riskmentioning
confidence: 99%
“…Currently, we lack detailed microclimate profiles for most bat box designs, but several studies have documented temperatures >40°C (maximum roost temperature: >40°C, Bartonička & Řehák, 2007; >50°C, Bideguren et al, 2018; 53°C, Brittingham & Williams, 2000; 54.5°C, Flaquer et al, 2014; 53°C, Griffiths, Rowland, et al, 2017; 61°C for a bark mimic roost, Hoeh, Bakken, Mitchell, & O'Keefe, 2018; >40°C, Kerth, Weissmann, & König, 2001; >50°C, Lourenço & Palmeirim, 2004; 54°C, Tillman, 2019), highlighting that many bat box designs could subject bats to heat stress. Exacerbating this, most published research has focused on novel box designs or modifications, providing data that are less applicable to practitioners and homeowners who are not intent on building or modifying their own boxes.…”
Section: Increasing Popularity Uncertainty and Riskmentioning
confidence: 99%
“…In Portugal, temperatures of artificial roosts painted black (vs. white or gray) were most comparable to building roosts and had the highest use by bats 42 . In the USA, the “rocket” box, which was the largest roost, remained within the critical temperature thresholds the greatest proportion of time 67 . In Australia 68 , found that bat box colour, chamber sequence, construction materials, and vents influenced internal temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The localised cooling effect in the lower section of the chamber was likely due to the chamber's vent. A previous study conducted in the Midwest region of the USA also documented temperature differences within boxes [61]. They found that two of their box designs could differ by more than 10 • C between upper and lower portions of the boxes during warm and clear days.…”
Section: Multiple Chambers and Ventsmentioning
confidence: 91%
“…It is unclear if short durations of temperatures over 40.0 • C are detrimental to bats [50,51,66] and likely varies between species and location [19,49]. Some bat box studies conducted in warm climates have raised concerns that bat boxes become lethal during hot ambient conditions [41,56], with Hoeh et al [61] recording box temperatures of up to 61 • C. The data obtained in this study indicates that at the study site, box temperatures experienced in black boxes (with an afternoon sun aspect) installed on poles with a natural groundcover underneath, were suitable for bats on an average summer day (mean maximum: 29.7 • C). However, during spells of very hot ambient temperatures or in climates experiencing warmer ambient temperatures to that at the study site, the availability of box designs buffering from very hot ambient temperatures and providing a thermal gradient are important.…”
Section: Thermal Limits and Box Temperaturementioning
confidence: 99%